2003
DOI: 10.1016/j.lts.2003.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical reactivation of hepatitis B virus in liver transplant recipients with past exposure

Abstract: Transmission of hepatitis B infection has been reported in liver transplant recipients whose donor livers were negative for hepatitis B surface antigen (HBsAg) and positive for antibody to hepatitis B core antigen (anti-HBc). These infections usually have a mild clinical course and no adverse effects on survival. However, the outcome of liver transplant recipients with serologic evidence of past infection to hepatitis B virus (HBV) is unknown. The prevalence of HBV DNA positivity by polymerase chain reaction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 25 publications
2
54
0
Order By: Relevance
“…In addition, loss of antiHBs is not uncommon following LT, even in patients with previous HBV exposure. One study reported the loss of anti-HBs post LT in 31% patients with pretransplant antiHBs and anti-HBc (14). Our patient experienced loss of antiHBs after LT despite short-term HBIg treatment and the presence of pre-LT anti-HBs.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In addition, loss of antiHBs is not uncommon following LT, even in patients with previous HBV exposure. One study reported the loss of anti-HBs post LT in 31% patients with pretransplant antiHBs and anti-HBc (14). Our patient experienced loss of antiHBs after LT despite short-term HBIg treatment and the presence of pre-LT anti-HBs.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, donor anti-HBs status does not need to be considered when assessing risk for de novo post-LT HBV infection. In addition, the presence of anti HBc (in the absence of hepatitis B surface antigen (HBsAg)) in the recipient prior to transplantation has negligible risk for post-LT HBV infection (13) even in the presence of hepatitis B virus deoxyribonucleic acid (HBV DNA) in the recipient serum or liver tissue (14).…”
Section: Introductionmentioning
confidence: 99%
“…With the development of sensitive molecular tests for HBV in recent years, in various clinical situations low levels of HBV DNA have been detected despite the absence of HBsAg: (a) Transmission trough transfusion 14,15 or transplantation 16,17 (b) Viral reactivation in patients under condition of immunosuppression. 18,19 (c) Chronic hepatitis of unknown aetiology, 4 in HCC 20 and the highest prevalence in HCV patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of occult HBV infections have reported that the frequency of HBV DNA was higher in liver than in sera. 5,17,26 However, in some case of occult HBV infection, HBV DNA was positive in serum but not detected in the liver. Alternatively, other locations may support on-going HBV replication.…”
mentioning
confidence: 99%
See 1 more Smart Citation